Digitalisasi Proses Analisis PEARLS Pada Koperasi Kredit (Studi Kasus: Puskopdit Handriya Sanggraha) - Matius Stephen Saputera; Desi Pibriana (Universitas Multi Data Palembang, 2026)
Puskopdit Handriya Sanggraha is a secondary cooperative tasked with monitoring the financial health of its member credit unions. Currently, the financial health assessment process using the PEARLS method (Protection, Effective Financial Structure, Asset Quality, Rates of Return and Costs, Liquidity, Signs of Growth) is conducted manually using separate spreadsheets. This process often leads to reporting delays, data input errors, and difficulties in real-time monitoring. For this reason, a web-based information system was built to automate PEARLS analysis so that it can centrally integrate the input of balance sheets, monthly data, and economic parameters. The development method used is Waterfall. The result of this research is a system that automates the calculation of 18 PEARLS indicators and presents financial health analysis results in real-time. The implementation of this system can increase reporting efficiency, calculation accuracy, and assist management in making strategic decisions based on valid cooperative health data.